Solar powered drip irrigation: Lessons learned from an impact evaluation in Yemen - Jovanovic, Nina; Darwish, Maram; Kurdi, Sikandra; Yamauchi, Futoshi (International Food Policy Research Institute, 2025)
This policy note summarizes findings from a clustered randomized controlled trial (RCT) conducted in eastern Yemen to assess the impacts of subsidized solar powered drip irrigation systems on smallholder farmers’ production decisions and household food security. The study provides causal evidence on how subsidizing solar drip irrigation for smallholders affects crop choice, market engagement, and welfare outcomes in a fragile, water-scarce context. The intervention led to a significant shift in cropping patterns, with treated farmers becoming less likely to cultivate cereals and more likely to grow higher-value horticultural crops. Treated households also sold a greater share of their harvest in markets during the first season following installation, suggesting increased commercialization. However, the study did not detect significant short-term impacts on household food security, indicating that production changes did not immediately translate into improved consumption outcomes.